The F-0 exuvia of Micrathyria almeidai Santos, 1945 (Odonata: Libellulidae) - Dias-Oliveira, Tomás Matheus; Santos, Jean Carlos; Urso-Guimarães, Maria Virginia; Vilela, Diogo Silva (Zootaxa, 2025)
Here, we describe, illustrate, and diagnose the F-0 exuvia of Micrathyria almeidai Santos, 1945, collected from the Serra do Japi Municipal Biological Reserve, Jundiaí, São Paulo, Brazil (23°14’10″ “S 46°57’11” W, 1053m asl) inhabiting lentic environments. The exuvia can be distinguished from other congeners based on the morphology of the mandibula and prementum.